2020
DOI: 10.1038/s41419-020-2733-4
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of microglia exacerbates injury and impairs function recovery after spinal cord injury in mice

Abstract: The role of microglia in spinal cord injury (SCI) remains ambiguous, partially due to the paucity of efficient methods to discriminate these resident microglia with blood-derived monocytes/macrophages. Here, we used pharmacological treatments to specifically eliminate microglia and subsequently to investigate the response of microglia after SCI in mice. We showed that treatment with colony stimulating factor 1 receptor (CSF1R) inhibitor PLX3397 eliminated ~90% microglia and did not affect other cell types in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…Microglia, astrocytes and oligodendrocyte are the main glia cells in the brain ( 96 ). These cells control the microenvironment of CNS neurons and are crucial in synaptic remodeling, tissue repair, and neuronal survival following CNS injury ( 97 100 ). Neuroinflammation stimulates the local activation of glia cells surrounding damaged or infected neurons.…”
Section: Neuroinflammation: At the Center Of The Infectious Hypothesimentioning
confidence: 99%
“…Microglia, astrocytes and oligodendrocyte are the main glia cells in the brain ( 96 ). These cells control the microenvironment of CNS neurons and are crucial in synaptic remodeling, tissue repair, and neuronal survival following CNS injury ( 97 100 ). Neuroinflammation stimulates the local activation of glia cells surrounding damaged or infected neurons.…”
Section: Neuroinflammation: At the Center Of The Infectious Hypothesimentioning
confidence: 99%
“…Although unclear how COX-1 can impact persons with SCI, COX-1 is highly associated with other neurological disorders including neuroinflammation (Choi et al, 2008;Aid et al, 2010;Choi et al, 2010), Alzheimer's disease (Yermakova et al, 1999), and ischemia (Schwab et al, 2000b). Microglia are vital neuroprotective components of our central nervous system (CNS) (Streit, 2005), preventing neuron and oligodendrocyte death (Bellver-Landete et al, 2019), stripping synapses (Chen and Trapp, 2016), and increasing spinal cord repairs (Fu et al, 2020;Li et al, 2020a). Microglia can also secrete Interferon (IFN)-β to remove axon and myelin debris from the injury site (Kocur et al, 2015), increase axon regenerative potential, and improve functional locomotor recovery (Tanaka et al, 2009).…”
Section: Acute Inflammatory Changes In the Spinal Cord Following Scimentioning
confidence: 99%
“…Second, using CCR2 null mice, it had been shown that stopping the crosstalk between resident microglia and monocyte derived macrophages participates in long-term microglial activation, greater myelin loss that eventually worsen motor function after SCI [5]. Third, complete microglia depletion altered glial scar formation, decreased immune infiltration, neuronal and oligodendrocytes survival associated with impaired motor recovery following SCI in mice [18,20]. This difference as compared to our findings may result from the specific subpopulation of microglia (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…PLX5622 treatment for 6 weeks post-SCI, improved cognition and depressive-like behavior recovery but did not improve the overall locomotor activity even if the regularity index and stride length were enhanced at 6 weeks following moderate/severe T10 contusion [60-70kdyn] [19]. PLX3397, another specific CSF1R inhibitor, given to mice between 7 days prior to complete T10 crush injury and 4 weeks after lesion impaired locomotor recovery, disorganized glial scar formation, increased lesion size, and reduced neuronal survival [20].…”
Section: Introductionmentioning
confidence: 99%